MODEL PEMBELAJARAN TEKNOLOGI INFORMASI DAN KOMUNIKASI PADA SEKOLAH LANJUTAN TINGKAT PERTAMA - Setyowibowo, Sigit (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2012)
The use of computers today are not just limited to the processing and manipulation of data alone but can also be used to create application programs related to education, especially the lessons of ICT by using a recorded human voice first. The purpose of this study was to create a learning application program of ICT in an interactive and communicative-based computer so that in the learning process is expected to run in both directions. The program also aims to reduce the saturation of the students in receiving the material being taught. Software (software) to program a computer learning aids Information and Communication Technology was created using Macromedia Flash program. Keywords: Help Program, Information and Communication Technology, Macromedia Flash